Histamina facilita a aprendizagem em uma tarefa de escolha espacial em Carassius auratus - Santos, Fernanda Romaguera Pereira dos (2006)
This work intended to investigate in forebrain ablated Carassius auratus the effect of the H1 receptor blockade in a spatial choice task using a T-maze test with positive reinforcement. Sixty-nine goldfish were submitted to surgery for removal of both telencephalic lobes five days before the beginning of the experiment. A T-shaped glass aquarium, which had two feeders located at the extremities of the long arm, was employed. One of the two feeders was blocked. The experimental trials were performed in nine consecutive days. Each fish was individually placed in the short arm and confined there for thirty seconds, then it was allowed to swim through the aquarium to search for the food for ten minutes (maximum period). Time to find food was analysed in seconds. Animals were injected intraperitoneally with chlorpheniramine (CPA) at 16 mg/kg of body weight or saline after every trial, ten minutes after it had been replaced at house aquarium. Data were analyzed via a three-way analysis of variance (ANOVA) with repeated measures, and post hoc comparisons were analyzed using the Student Newman-Keuls test (p<0.05). All the training latencies of A-SAL group were significantly higher than latencies of S-SAL group (p<0.05). S-SAL group showed a significative decrease in latencies at the second trial and maintained that reduction until the end of the experiment (p<0.05), S-CPA group demonstrated a decrease only after the fourth trial (p<0.01), A-SAL group showed reduced latencies after the fifth trial (p<0.05), and ACPA group did not showed any difference between training latencies. Thus, our results showed that CPA seems to impair the consolidation of memory either on telencephalon ablated animals and in sham-operated ones. Furthermore, this work supports evidence that histamine plays a facilitatory role in learning and memory processes of a spatial task through its action in primitive structures of the brain in teleost fish.